The Role of Akidah Akhlak Teachers in Fostering Students’ Good Character in MTs Negeri 1 Tanjungkarang - Putra, Joni; Saputri, Rima Yuni (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2022)
The background of the problem in this research was the importance of teacher’s role in fostering the good character of students. Based on the results of preliminary research, there were still many students who showed bad attitudes such as fighting, not wanting to help friends who were having difficulties, being ignorant, and so on. This study used a qualitative method and the data sources in this study included teachers of Akidah Akhlak subject, school principal, and students. Data collection techniques were carried out through observation, interviews, and documentation. The data analysis technique was inductive and described narratively. The results of this study indicated that the teachers of Akidah Akhlak at MTs Negeri 1 Tanjungkarang generally have carried out their roles quite well, especially in fostering the good character of the students.